A Successful Case of Intervention for Traumatic Central Retinal Artery Occlusion - Mohsen Pourazizi; Alireza Dehghani; Sepehr Karbasi; Elham Rahmanipour (Case Reports in Ophthalmology)
Introduction: Central retinal artery occlusion (CRAO) is a serious ophthalmic disease predominantly affecting older individuals with cardiovascular risk factors. While most cases are attributed to thrombus formation from atheromatous plaques or cardioembolic events, trauma-related CRAO, though rare, presents unique diagnostic and therapeutic challenges. Case Presentation: A 47-year-old woman with multiple controlled comorbidities presented to the emergency department with right eye pain and erythema following a traumatic injury involving a knitting needle. Initial examinations revealed hand motion visual acuity in the right eye, a partial thickness scleral laceration, and conjunctival laceration, which were surgically repaired. Postoperatively, she developed blurred vision, hyphema, and signs of CRAO, prompting anterior chamber paracentesis. OCT imaging revealed marked hyperreflectivity and thickening of the inner retinal layers, indicating significant ischemic damage. Despite normal inflammatory markers, the patient’s visual acuity gradually improved from 2/10 to 5/10 with intervention and eventually reached 10/10 with myopic correction after the hyphema resolved. Conclusion: The case emphasizes the necessity of early recognition and intervention in managing traumatic CRAO to mitigate irreversible retinal damage. It underscores the need for enhanced diagnostic and therapeutic strategies as understanding the condition’s pathophysiology advances.